Two decades of live coding and debugging of virtual machines through simulation. (8th May 2020) - Ingalls, Daniel; Miranda, Eliot; Béra, Clément; Gonzalez Boix, Elisa
Summary: OpenSmalltalk‐VM is a virtual machine (VM) for languages in the Smalltalk family (eg, Squeak and Pharo), which is itself written in a subset of Smalltalk that can easily be translated to C. VM development is done in Smalltalk, an activity we call "simulation." The production VM is then derived by translating the core VM code to C. As a result, two execution models coexist: simulation, where the Smalltalk code is executed on top of a Smalltalk VM, and production, where the same code is compiled to an executable through a C compiler. The whole VM execution can be simulated: the heap is represented as a huge byte array, the VM code is executed as Smalltalk, and the native code generated by the just‐in‐time (JIT) compiler is executed by a processor simulator. All the Smalltalk development tools, such as the debugger, are then available while simulating. In addition, in simulation, it is also possible to use debugging features such as single stepping in the machine code generated by the JIT compiler. The Smalltalk development tools combined with the simulation debugging features provide developers with a productive environment in which to extend and debug the VM. In this article, we detail the VM simulation infrastructure and report our experiences developing and debugging VM features within it such as the garbage collector and the JIT compiler.